2019
DOI: 10.1016/j.omtn.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Kinetics of Lipid-Nanoparticle- Mediated Delivery of Multiple siRNAs to Evaluate the Effect on Competition for Ago2

Abstract: Drug combinations can improve the control of diseases involving redundant and highly regulated pathways. Validating a multi-target therapy early in drug development remains difficult. Small interfering RNAs (siRNAs) are routinely used to selectively silence a target of interest. Owing to the ease of design and synthesis, siRNAs hold promise for combination therapies. Combining siRNAs against multiple targets remains an attractive approach to interrogating highly regulated pathways. Currently, questions remain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…In summary, we have demonstrated that when modified with large amine molecules such as PAMAM dendrimers, pSiNPs showed favorable loading and release kinetics for siRNA. We have defined favorable release kinetics as a slow sustained release rate as the slow release of siRNA into the cytoplasm may be more beneficial in order to prevent saturation of argonaute-2 (AGO2)avoiding competition between strands of siRNA . Thus, we established that a sustained siRNA release profile over 72 h was appropriate for gene silencing via intravenous delivery.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, we have demonstrated that when modified with large amine molecules such as PAMAM dendrimers, pSiNPs showed favorable loading and release kinetics for siRNA. We have defined favorable release kinetics as a slow sustained release rate as the slow release of siRNA into the cytoplasm may be more beneficial in order to prevent saturation of argonaute-2 (AGO2)avoiding competition between strands of siRNA . Thus, we established that a sustained siRNA release profile over 72 h was appropriate for gene silencing via intravenous delivery.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Arcturus Therapeutics, 173 Dicerna Pharmaceuticals, 174 Silence Therapeutics, 175,176 Sirna Therapeutics (acquired by Alnylam from Merck & Co., Inc. in 2014) 177,178 and Suzhou Ribo Life Science 142 also made great efforts to develop lipid-based siRNA delivery systems, some of which have been advanced to the clinical stage.…”
Section: Sirna Modificationmentioning
confidence: 99%
“…However, the often poor delivery efficiency of siRNA into the cytoplasm via endocytosis is balanced by the fact that gene silencing using siRNA is an efficient process, in which a single siRNA molecule can elucidate a long‐lasting gene silencing effect (Figure 2). [ 50 ] Once the siRNA is introduced into the cell cytoplasm, double‐stranded RNA (dsRNA) incorporates into a multi‐protein complex, named, RNA‐induced silencing complex (RISC), in order to activate the RNAi pathway. [ 51 ] Once integrated, the dsRNA is unwound, forming two single‐stranded RNA molecules, the sense and antisense strand.…”
Section: Barriers To Overcomementioning
confidence: 99%